Law Matters - John N. Drobak (Washington University Law Quarterly, 1998)
Neoclassical economic theory has attributed modem economic growth to a combination of factors: human capital (the amount and skill of labor), physical capital (machines, factories, agricultural improvements, etc.), natural resources, technology (human command over nature), and the stock of knowledge (the understanding of the natural environment). Over the past few decades, some economists have begun to emphasize the importance of one additional component: institutions. These are the "rules of the game" of a society. Institutions can be informal or formal. Informal institutions include such things as norms of behavior, cultural constraints, codes of conduct and business conventions. Some formal institutions are created by nongovernmental organizations-religious laws, corporate rules of self-governance and use restrictions imposed by residential groups are some examples. The most important formal institutions, however, are legal, such as constitutions, statutes, regulations and decisions of courts and agencies.
Keywords: Rule of law; Law & amp; economics; Legal philosophy